Cardiovascular safety of antipsychotics: a clinical overview. Issue 5 (3rd May 2016) - Polcwiartek, Christoffer; Kragholm, Kristian; Schjerning, Ole; Graff, Claus; Nielsen, Jimmi
ABSTRACT: Introduction : Although antipsychotics have been associated with sudden cardiac death (SCD), they still remain a cornerstone in the treatment of psychiatric patients. Most antipsychotics have an unfavorable cardiovascular adverse effect profile, and SCD may occur even in patients with no cardiovascular risk factors. Areas covered : This clinical overview summarizes the cardiovascular safety of antipsychotics by focusing on the wide range of associated adverse effects. In addition, we also discuss current guidelines regarding routine electrocardiogram (ECG) monitoring. Expert opinion : As SCD in psychiatric patients is multifactorial, the contribution from antipsychotic treatment remains largely unknown. Cardiovascular adverse effects of antipsychotics vary substantially, even when used in therapeutic doses. Currently, most clinical concern focuses on antipsychotic-induced corrected QT prolongation, as this may increase risk of Torsades de Pointes and eventually SCD. However, other serious cardiovascular adverse effects of antipsychotics also include Brugada syndrome phenotype, myocardial infarction, and myocarditis. Increased awareness of the cardiovascular safety of antipsychotics can allow physicians to better manage and monitor high-risk patients. In this patient group, ECG monitoring may be warranted and other examinations symptom driven. Prescription of antipsychotics should always be a balance between the perceived clinical effect and the burden of adverse effects.